Analisis Perbandingan Kinerja Keuangan Bank Umum Syariah Di Indonesia Sebelum Dan Sesudah Covid 19 - Alfia Dwi Damayanti; Herudini Subariyanti (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
The Covid-19 pandemic is a problem for banks because it can cause problems in the real sector or potential problems for the business world in the banking sector. This of course can happen, because the banking sector is an intermediary or intermediary institution supporting the needs of investment funds in the business world. The data analysis method in this study uses quantitative analysis with a comparative approach which aims to determine differences in the financial performance of Islamic commercial banks before Covid-19 and after Covid-19 using the indicators ROA, CAR, BOPO, NPF and FDR. The source of data in this study is secondary data, in which researchers obtain financial performance data from financial reports contained in OJK. The results of this study indicate that the financial performance of Islamic Commercial Banks compared to before Covid-19 has decreased in the financial ratios ROA, FDR, BOPO after Covid-19 while the ratio of CAR, NPF after Covid 19 has increased compared to before Covid-19.